2017
DOI: 10.20870/oeno-one.2017.51.2.1586
|View full text |Cite
|
Sign up to set email alerts
|

Multi-seasonal effects of warming and elevated CO<sub>2</sub> on the physiology, growth and production of mature, field grown, Shiraz grapevines

Abstract: Industry concerns in Australia about the impacts of climate change have, to date, focused on the effects of warming, particularly shorter maturation periods. The effects of elevated CO 2 concentration (eCO 2 ) on C 3 plant physiology have been extensively studied and suggest that eCO 2 impacts on viticulture could affect grapevine shoot growth, fruit production and fruit composition. We previously used open top chambers (OTC) with an active heating system to study the effects of elevated air temperature (eTemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 9 publications
2
22
0
Order By: Relevance
“…Interestingly, Bindi et al [7] demonstrated that TSS of Sangiovese was stimulated by eCO 2 during ripening, but the positive effect disappeared when grapes reached maturity. Gonçalves et al [2] also confirmed this for Touriga Franca, whereas only Edwards et al [5] indicated that eCO 2 resulted in a higher TSS accumulation for Shiraz at harvest. Berries of both cultivars reached a higher sugar concentration for both treatments at maturity in 2015 compared to the other seasons.…”
Section: Berry Developmentmentioning
confidence: 92%
See 3 more Smart Citations
“…Interestingly, Bindi et al [7] demonstrated that TSS of Sangiovese was stimulated by eCO 2 during ripening, but the positive effect disappeared when grapes reached maturity. Gonçalves et al [2] also confirmed this for Touriga Franca, whereas only Edwards et al [5] indicated that eCO 2 resulted in a higher TSS accumulation for Shiraz at harvest. Berries of both cultivars reached a higher sugar concentration for both treatments at maturity in 2015 compared to the other seasons.…”
Section: Berry Developmentmentioning
confidence: 92%
“…CO 2 enrichment increases photosynthesis and, therefore, growth and yield of perennial plants. Within grapevines, this was already shown by various authors using different CO 2 enrichment techniques such as open top chambers [2][3][4][5], Mini-FACE (Free-Air Carbon Dioxide enrichment) [6][7][8], or the recently reported VineyardFACE system [9,10]. In addition to open field studies on grapevines, CO 2…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Elevated CO 2 concentration (eCO 2 ) is one of the main drivers of climate change ; however, its impact on the bud fertility of field-grown grapevines has not yet been investigated. Studies that focused on the influence of eCO 2 on grapevines, particularly in the field, have shown increased vegetative and fruit biomass under eCO 2 , due to higher rates of photosynthesis (Bindi et al, 2001 ;Moutinho-Pereira et al, 2009 ;Edwards et al, 2017 ;Wohlfahrt et al, 2018). Although eCO 2 had no effect on the number of bunches per vine, bunch and berry weight were increased (Bindi et al, 1996 ;Moutinho-Pereira et al, 2009 ;Wohlfahrt et al, 2018).…”
Section: Introductionmentioning
confidence: 99%